2021
DOI: 10.1038/s41392-021-00746-6
|View full text |Cite
|
Sign up to set email alerts
|

BUB1B and circBUB1B_544aa aggravate multiple myeloma malignancy through evoking chromosomal instability

Abstract: Multiple myeloma (MM) is an incurable plasma cell malignancy in the bone marrow characterized by chromosome instability (CIN), which contributes to the acquisition of heterogeneity, along with MM progression, drug resistance, and relapse. In this study, we elucidated that the expression of BUB1B increased strikingly in MM patients and was closely correlated with poor outcomes. Overexpression of BUB1B facilitated cellular proliferation and induced drug resistance in vitro and in vivo, while genetic targeting BU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 62 publications
0
20
0
Order By: Relevance
“…Among these hub genes, MAD2L1, TOP2A, NCAPG, TTK, KIF11, HELLS, and RRM2 may affect biological changes after receiving second messengers from activated BUB1B, DTL, and CDK1. BUB1B encodes a kinase involved in spindle checkpoint function, whose impairment is associated with various cancers ( 27 30 ). CDK1 encodes the catalytic subunit of a highly conserved protein kinase complex that is required for the G1/S and G2/M phase transitions of the eukaryotic cell cycle.…”
Section: Discussionmentioning
confidence: 99%
“…Among these hub genes, MAD2L1, TOP2A, NCAPG, TTK, KIF11, HELLS, and RRM2 may affect biological changes after receiving second messengers from activated BUB1B, DTL, and CDK1. BUB1B encodes a kinase involved in spindle checkpoint function, whose impairment is associated with various cancers ( 27 30 ). CDK1 encodes the catalytic subunit of a highly conserved protein kinase complex that is required for the G1/S and G2/M phase transitions of the eukaryotic cell cycle.…”
Section: Discussionmentioning
confidence: 99%
“…We have identified BUB1B, NUSAP1, TTK, HMMR, CCNA2, and KIF2C as potential predictive markers for HCC. Previous studies indicate that expression levels of BUB1B, which is a spindle-assembly checkpoint gene [ 26 ], were highly upregulated in multiple myeloma patients and that these levels were strongly correlated with unfavorable outcomes [ 27 ]. Another marker, NUSAP1, which is a microtubule-associated protein involved in mitosis, is also known to participate in cell proliferation, apoptosis, and repairing DNA damage in glioblastoma multiforme cells [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pure-hybrid BUB1B mutations could lead to autosomal recessive gastrointestinal cancer susceptibility [32]. Further, BUB1B expression was signi cantly increased in patients with multiple myeloma and was strongly associated with poor outcomes [33]. In another study, BUB1B was shown to be a predictive marker for aggressiveness and effective drug response in glioblastoma [34].…”
Section: Discussionmentioning
confidence: 99%